PHYTOCHEMICALS DETECTION, ANTIOXIDANT AND ANTIMICROBIAL ACTIVITY STUDY ON BERRIES OF SOLANUM TORVUM - Christi Ve, Ida; Poorani T, Uma; G, Nagarajaperumal; S, Mohan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This present study is planned to reveal about the pharmacognostical details, phytochemistry, antimicrobial activity, and antioxidant activity of aqueous and alcoholic extract of the berries of Solanum torvum Swartz. belonging to the family Solanaceae, which is a very good anti-inflammatory medicine in traditional system of therapies. Methods: The physicochemical parameters such as ash values, extractive values, and total fiber content, qualitative preliminary phytochemical studies, quantitative estimation for total phenolic contents and flavonoid content, anjd inorganic minerals such as sodium, calcium, and potassium were estimated. Flavonoids present in the methanolic extract were isolated and its Rf values were calculated by high-performance thin-layer chromatography method and compared with that of the standard epicatechin. The antioxidant activity was evaluated by Reducing power ability, 1, 1-diphenyl-2-picrylhydrazyl method, and hydrogen peroxide methods. The antibacterial and antifungal activities of the aqueous and methanolic extracts are evaluated by disc diffusion method comparing the zone of inhibition with that of the standards such as amikacin and Ketoconazole. Results: It contains a number of potentially pharmacologically active chemicals including the sapogenin steroid, chlorogenin, alkaloids, flavonoids, phenols, and tannins. Both the extracts showed good activity, but the alcohol extract is more active toward all bacterial organisms and also toward fungi organism. Methanol extract shows good antioxidant activity. Antimicrobial activity and antioxidant activity of the berries are due to the presence of phytoconstituents present in it. Conclusion: These berries can be used for new formulation in nutraceuticals and polyherbal natural formulations for reducing the oxidative stress-related diseases and different therapies.